Latent Thermal Energy Storage for Cooling Demands in Battery Electric Vehicles: Development of a Dimensionless Model for the Identification of Effective Heat-Transferring Structures - Volker Dreißigacker; Andrea Gutierrez (Energies)
Thermal energy storage (TES) systems open up alternative paths for air conditioning to increase the range of battery electric vehicles (BEVs) by reducing power consumption. The central prerequisites for this purpose are high storage densities: high-temperature TES systems are being focused on for heat demands, while effective solutions for cooling are missing. Due to their lower temperature potentials, concepts with high storage capacities and heat transports between the storage and cold transferring medium are needed. Latent TES systems based on water enable these capacities but require adequate internal structures for effective heat transfer. Due to the large number of geometric options, high simulation efforts must be conducted to identify favored structures, or the possible design space must be limited for investigations. For this purpose and for the first time, an alternative way is presented using newly developed dimensionless models in a top-down methodology for time-efficient design studies and evaluations. These models were successfully validated and used as a design tool to identify effective structures in latent TES systems for cooling demands in BEVs. A wide array of variation studies on tube, finned plate and novel Triply Periodic Minimal Surface (TPMS) structures were performed and uniformly evaluated with regard to storage densities, cooling efficiencies and geometry. The results show high storage densities for novel TPMS structures, including the enclosure of 100 Wh/kg or 102.2 kWh/m3 with average cooling capacities of 1 kW over 30 min, confirming the usability of latent TES systems in terms of compactness and efficiency for cooling demands in BEVs.